INDIAN KALINGA STYLE TEMPLE ARCHITECTURE OF SOME HINDU TEMPLES OF EASTERN ODISHA - Mohapatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
The region of the eastern part of Odisha is well-known for its historic antiquities and religious sanctuaries in India. This place not only attracts the scholars but also draws the attention of the art historians. All the extant temples of Eastern Odisha represent the Kalinga style temple architecture of India. Although the Nilakanthesvara temple of Denua is certainly a Saiva shrine, here we can find a series of Vaishnavite deities preserved for the purpose of worship. The available Vaishnavite images in the temple site are an interesting study for the present scholars to know the peculiarity of the temple. Most of the detached sculptures of the temple contain the iconographic features of the Ganga art of Odisha. Though the Buddhakesvara temple is dedicated to Lord Buddhesvara Shiva, still its sanctum preserves the Vashnavite images of Radha-Krishna. It suggests that the temple site is a coordinating place of Saivism and Vaishnavism of the Hindu pantheon. There is a fine, detached image of a Buddhist goddess found in the northwest corner of the temple premises of Lord Trivenisvara. It is very interesting for the scholars and antiquarians for deep study. The sanctum of the Durga temple of Narishop preserves the image of Goddess Manasa as the chief deity for public worship. But this Manasa image is being worshiped by the local people as Goddess Durga. The present article attempts to highlight the art techniques and architectures with the religious importance of the Nilakanthesvara temple of Denua, Buddhsvara temple of Garhkaramala, Trivenisvara temple at Tiruna, and Durga temple at Narishoof in Eastern Odisha. Both the primary and secondary sources are methodologically utilized in the writing of the present article.